Effects of end milling cutting parameters and lubrication modes on residual stress and surface quality in medium carbon steel machining / Nik Masmiati binti Nik Pa - Nik Pa, Nik Masmiati (2015)
Residual stresses play an important role in the performance of machined components. Tensile residual stress on the surface of a component is undesirable. It causes fatigue failure, quench cracking and stress corrosion cracking. Meanwhile, compressive residual stress is usually beneficial to surface layers as it increases fatigue strength and resistance to stress corrosion cracking. To measure tensile and compressive residual stresses on machined surfaces and beneath, x-ray diffraction (XRD) is used. This research focuses on inclined and flat end milling. An initial study was conducted to investigate only numerical factors, such as machined surface inclination angle, axial depth of cut, spindle speed and feed rate in the inclined end milling process. The Taguchi optimization method was used to achieve the best cutting parameter level for minimum residual stress, surface roughness and maximum microhardness. The optimum condition results obtained through analysis show improvements in residual stress in the feed direction of about 18.6% and in the cutting direction 15.4%, microhardness 0.7% and surface roughness 12.3%. Further research was done to investigate the effect of categorical factors, namely milling and lubrication modes on residual stress and surface quality in flat end milling. Both lubrication and milling modes have the potential to increase the thermal gradient and plastic deformation during milling. The milling modes used were conventional (up) milling and climb (down) milling. Employing flood lubrication can improve the residual stress and surface integrity of a component; however, it has great environmental impact. Minimum quantity lubrication (MQL) can serve as an alternative lubricant for clean machining and the addition of nanoparticles to MQL is expected to enhance machining performance and meet environmental standards. Results obtained showed that higher tensile residual stress was produced in down milling withMQL cutting compared to flood cutting due to insufficient cutting oil penetration into the tool-workpiece interface. However, the presence of SiO2 nanoparticles inMQL cutting improved the residual stress, which became more compressive. In up milling, higher compressive residual stress could be achieved using MQL-SiO2 nano-lubrication in cutting due to its cutting efficiency, as the rolling action of billions units of nanoparticles in the tool chip interface significantly reduces cutting force, friction and temperature. Finally, response surface methodology (RSM) with D-optimal experimental design was used to investigate the influence of both numerical and categorical factors during flat end milling of S50C medium carbon steel. Analysis of variance (ANOVA), interaction plot and response surface plot were used to determine the significant parameters and to obtain the individual and combined optimumcutting conditions for residual stress, cutting force and surface roughness. A mathematical model was developed to build the relationship between input parameters and output responses. The comparison showed good agreement between the predicted and experimental values.